Secondary Merkel Cell Carcinoma Manifested in the Parotid - M. Basati; K. Kassam; A. Messiha (Case Reports in Dermatological Medicine)
Background. Merkel cell carcinoma of the head and neck is a rare and aggressive malignant tumour. Both the dermatological and surgical colleagues should be aware of this entity as lesions usually present on sun exposed areas of the skin such as the head and neck. Main Observation and Treatment. A 69-year-old male originally presented to the maxillofacial surgery department with a growing lesion on the left eyebrow. Histological analysis confirmed Merkel cell carcinoma and consequently surgical excision was carried out. A follow-up PET/CT scan 2 years later demonstrated a hotspot in the left parotid gland. Fine needle aspiration and cytology revealed Merkel cell carcinoma. A subtotal parotidectomy left side with ipsilateral selective neck dissection levels I to III was carried out. Conclusions. Potential secondary Merkel cell carcinoma in the head and neck region should be taken into account when planning short- and long-term follow up for previously diagnosed patients. This followup should involve both dermatological and surgical colleagues.